The Macrophage Reprogramming Ability of Antifolates Reveals Soluble CD14 as a Potential Biomarker for Methotrexate Response in Rheumatoid Arthritis - Fuentelsaz-Romero, Sara; Barrio-Alonso, Celia; García Campos, Raquel; Torres Torresano, Mónica; Muller, Ittai B.; Triguero-Martínez, Ana; Nuño, Laura; Villalba, Alejandro; García-Vicuña, Rosario; Jansen, Gerrit; Miranda-Carús, María-Eugenia; González-Álvaro, Isidoro; et al. (Frontiers in Immunology, 2021)
The identification of “trained immunity/tolerance” in myeloid cells has changed our perception of the performance of monocytes and macrophages during inflammatory and immune responses. Pemetrexed (PMX) and methotrexate (MTX) are blockers of the one-carbon metabolism (OCM) and commonly used therapeutic agents in cancer and rheumatoid arthritis (RA). We have previously showed that MTX promotes trained immunity in human macrophages. In the present manuscript, we have assessed the anti-inflammatory effects of PMX and MTX and found that OCM blockers alter the functional and gene expression profile of human macrophages and that OCM blockade reprograms macrophages towards a state of lipopolysaccharide (LPS) tolerance at the signaling and functional levels. Moreover, OCM blockade reduced macrophage LPS responsiveness by impairing the expression of membrane-bound and soluble CD14 (sCD14). The therapeutic relevance of these results was later confirmed in early RA patients, as MTX-responder RA patients exhibit lower sCD14 serum levels, with baseline sCD14 levels predicting MTX response. As a whole, our results demonstrate that OCM is a metabolic circuit that critically mediates the acquisition of innate immune tolerance and positions sCD14 as a valuable tool to predict MTX response in RA patients.